Obsession [compact disc, unabridged] - Robards, Karen (Brilliance Audio, 2007)
"Katharine Lawrence has no idea what hit her. The attack came out of nowhere. Only hours earlier she had been enjoying a girls-only weekend with an old college friend. Now she finds herself lying bound and gagged on her kitchen floor, staring with terrified eyes at her friend Lisa while two masked gunmen search her house for-- what? She doesn't know"--Container.